Citing a Southeast Asian classic citation analysis of Vicente Rafael's contracting colonialism - Guillermo, Ramon G. (2013)
On an international plane, Contracting Colonialism by Vicente Rafael is probably one of the most successful historical works written by a Filipino. Since its publication, it has been widely cited in various disciplines such as Philippine studies, Southeast Asian studies, translation studies, Latin American studies, and various other fields. This paper aims to gain some insight into the extent and nature of its extraordinary influence, both Philippine and international, through citation analysis. However, a critical perspective is also offered on the issue of scholarly valuation through such citation analysis in relation to the Malaysian scholar Syed Farid Alatas’s proposal for an “autonomous social science.”
Keywords: Impact factor (Citation analysis); Literature reviews; Rafael, Vicente L